Analytical model for ore deposit evaluation. A surface mine project case application - Ortiz Sánchez, Oswaldo (2018)
This study presents a simplified analytical model for ore deposit evaluation for either an orebody in a stage of project or in actual exploitation. Model variables are average ore grades of contained metals, annual rate of ore mined and ore deposit reserves. The model estimates annual net cash income, return on investment and net value of the ore deposit at the investor’s fixed annual interest rate after discounting the total investment. An example of the model application is shown for a copper-zinc ore deposit mined by the open pit method. All three variables of the model are considered to be the most important factors and were chosen from a number of known variables of the annual income flow. The criteria for variables selection follow the 80/20 Pareto rule which shows that 20 percent of the factors account for 80 percent of the results. The surface mining method was chosen by comparing the critical waste to ore ratio of two low cost underground mining methods, with the surface mining system.